Vocational Students’ Mathematical Disposition: Post-Instruction Analysis of Vector Learning - Chyntia, Chyntia; Puspitasari, Nitta; Sundayana, Rostina (Department of Mathematics Education Program IPI Garut, 2025)
Penelitian ini bertujuan untuk menganalisis disposisi matematis siswa SMK setelah pembelajaran matematika semester genap 2024/2025, khususnya pada materi vektor. Penelitian dilakukan dengan pendekatan deskriptif kualitatif melalui triangulasi data dari observasi, angket skala Likert 57 siswa, dan wawancara mendalam terhadap enam siswa dari kategori disposisi tinggi, sedang, dan rendah. Fokus wawancara diarahkan pada lima indikator yang bernilai cukup, yakni pada indikator percaya diri; gigih dan tekun; minat dan rasa ingin tahu; memonitor dan merefleksi; serta bergairah dan serius dalam belajar. Hasil analisis menunjukan bahwa disposisi matematis siswa secara umum berada dalam kategori cukup, dengan variasi mencolok antarindividu. Studi ini melengkapi penelitian sebelumnya yang memberikan gambaran kontekstual dari siswa SMK yang kurang mendapat sorotan dalam kajian disposisi matematis. Peneliian ini juga menyoroti pentingnya intervensi guru dalam menciptakan lingkungan belajar yang mendukung eksplorasi, refleksi, dan keberanian berpikir, terutama dalam mengajarkan materi yang bersifat abstrak seperti vektor. This research aims to analyze the mathematical disposition of vocational high school students after the second semester of mathematics instruction in the 2024/2025 academic year, specifically on the topic of vectors. The research was conducted using a descriptive qualitative approach through data triangulation from observations, a 57-student Likert scale questionnaire, and in-depth interviews with six students from high, medium, and low disposition categories. The interview focused on five indicators considered quite valuable: self-confidence, persistence and perseverance, interest and curiosity, monitoring and reflection, and being enthusiastic and serious about learning. The analysis results show that students' mathematical disposition is generally in the sufficient category, with significant variation between individuals. This study complements previous research by providing a contextual overview of vocational high school students, who have received less attention in studies on mathematical disposition. This research also highlights the importance of teacher intervention in creating a learning environment that supports exploration, reflection, and the courage to think, particularly when teaching abstract material such as vectors.